Increasing Employee Engagement through Branding Activities of Corporate Learning Leaders - Lambert, Viktória; Gyökér, Irén (Marketing & Menedzsment, 2019)
PURPOSE OF THE STUDY The workplace learning environment and the responsibilities of learning leaders are increasingly important in the changing world of HR, as organizations recognize that they can maintain their competitive edge only if their employees are motivated to play an active part in the learning process. Our aim was to evaluate the role of learning leaders in this process, to offer a model of effectiveness in terms of the branding of corporate learning and to contribute to defining the critical indicator needed if investment in corporate learning is to be successful. RESEARCH METHOD We identified the corporate learning leader - i.e., Chief Learning Officer (CLO) - as playing the most important role in an elaborated model embracing all stakeholders in corporate education programs. We also examined the CLO’s role as ‘value creator’ in the learning enterprise model, focusing especially on the branding of the learning program. After reviewing the relevant literature, consulting with practitioners in industry, investigating the most important features relating to the branding of corporate learning programs and drawing on the most fundamental level of Kirkpatrick’s model, we conducted a web-based survey, with the aim of proposing a possible ranking order of effectiveness for these branding efforts. RESEARCH FINDINGS Learning leaders have an emerging value-creating role in identifying and engaging the most highly motivated employees - those willing to invest their own time in opt-in learning programs. This role is strengthened by branding these learning programs, and so we suggest a possible framework for prioritizing efforts in this direction, targeting tangible outcomes. These include such factors as the numbers of participants enrolled and indicators of effectiveness such as course completion rates and attendance at follow-up sessions. SUGGESTIONS Building on an assessment method of learning program branding activities, dimension-based branding activity attributes and their intensity, we suggest making these branding initiatives more conscious, so helping learning leaders to make their corporate learning program branding activities more comprehensive.